Implementation Strategy of Evidence-Based Practice in Nursing: An Integrative Review - Suyatno, La Ode Muhammad; Syahrul, Syahrul (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Evidence-based practice (EBP) in nursing practice is one way to solve nursing problems based on existing research evidence. Implementation of EBP must be organized properly so that the expected results are also good. This integrative review aimed to identify the literature implementing EBP and barriers to EBP implementation. An integrative review was conducted using the Whittemore and Knafi approach. Results: EBP can be implemented to overcome problems in nursing interventions, use new instruments, and test regulations related to nursing practice. Implementation of EBP using an appropriate framework can improve implementation outcomes. EBP can provide opportunities for nurses to solve problems encountered in nursing practice.